RI 4656 Deep-Well Pumps And Shaft Pumps In Anthracite Mines Of Pennsylvania - William H. Lesser (The National Institute for Occupational Safety and Health (NIOSH), 1950)
Never before have mine managers in the anthracite region of Pennsylvania been so seriously concerned about the rising cost of pumping mine water. Many of them know that future pumping charges may affect their operating profits adversely to an extent that will make it necessary to abandon some mines. Increased pumping charges in the anthracite industry are currently comparable in importance with higher mining costs; in fact, profitable operation of some mines depends not only upon the cost of mining coal but also upon whether they can be kept free from water at reasonable cost. Pumping charges are relatively low during the early development of a mine, but they increase rapidly as development progresses. Numerous crop falls, strippings, and. abandoned adjacent properties contribute unfavorably to the volume of water produced during mining. The foregoing conditions and the existence of large underground pools below existing mining levels present water problems of such magnitude and cost that some mine owners cannot continue to operate profitably.